Effect of oil overlay on inhibition potential of roscovitine in sheep cumulus-oocyte complexes - Crocomo, L. F. [UNESP]; Marques Filho, W. C. [UNESP]; Ulian, C. M. V. [UNESP]; Branchini, N. S. [UNESP]; Silva, D. T. [UNESP]; Ackermann, C. L. [UNESP]; Landim-Alvarenga, F. C. [UNESP]; Bicudo, S. D. [UNESP] (Wiley-Blackwell, 2015)
Contents Inhibitors of cyclin-dependent kinases, as roscovitine, have been used to prevent the spontaneous resumption of meiosis in vitro and to improve the oocyte developmental competence. In this study, the interference of oil overlay on the reversible arrest capacity of roscovitine in sheep oocytes as well as its effects on cumulus expansion was evaluated. For this, cumulus-oocyte complexes (COCs) were cultured for 20h in TCM 199 with 10% foetal bovine serum (Control) containing 75m roscovitine (Rosco). Subsequently, they were in vitro matured (IVM) for further 18h in inhibitor-free medium with LH and FSH. The culture was performed in Petri dishes under mineral oil (+) or in 96 well plates without oil overlay (-) at 38.5 degrees C and 5% CO2. At 20 and 38h, the cumulus expansion and nuclear maturation were evaluated under stereomicroscope and by Hoechst 33342 staining, respectively. No group presented cumulus expansion at 20h. After additional culture with gonadotrophins, a significant rate of COCs from both Control groups (+/-) exhibited total expansion while in both Rosco groups (+/-) the partial expansion prevailed. Among the oocytes treated with roscovitine, 65.2% were kept at GV in the absence of oil overlay while 40.6% of them reached MII under oil cover (p<0.05). This meiotic arrest was reversible, and proper meiosis progression also occurred in the Control groups (+/-). So, the culture system without oil overlay improved the meiotic inhibition promoted by roscovitine without affecting the cumulus expansion rate or the subsequent meiosis progression.